APLIKASI BERBASIS AUGMENTED REALITY (AR) UNTUK JENIS KEMASAN PRODUK UMKM - Arianto Chandra; Muhammad Sabir Ramadhan (LPPM STMIK Royal Kisaran, 2023)
Abstract: The product packaging plays a crucial role in attracting consumers' attention and enhancing the value of a product, especially for small and medium enterprise (SME). However, SME often face limitations in designing attractive and innovative packaging due to resource constraints and limited graphic design knowledge. Therefore, this research aims to develop an Augmented Reality (AR)-based application that can assist SME in designing more appealing and impactful product packaging. The result of this research is an AR application that can be downloaded and used by SME to simplify the consultation process with advisors at the Coal Packaging House. One common issue is the distance limitation for consulting on the type of packaging to be created, which can be overcome with this AR application. This AR application enables SME to choose their product packaging types in interactive 3D forms, allowing them to explore various packaging designs and select the most suitable one for their products. Initial evaluations indicate that this AR application can support SME in consulting with advisors at the Coal Packaging House, thus improving their product packaging designs, increasing product appeal, and ultimately boosting sales. Additionally, this application also positively contributes to SME understanding of AR technology and better packaging design. This research also contributes to our understanding of how AR technology can be utilized to support SME.Keyword: Augmented Reality (AR); SME; Packaging. Abstrak: Kemasan produk memiliki peran penting dalam menarik perhatian konsumen dan meningkatkan nilai jual suatu produk, terutama untuk Usaha Mikro, Kecil, dan Menengah (UMKM). Namun, UMKM seringkali menghadapi keterbatasan dalam merancang kemasan yang menarik dan inovatif karena keterbatasan sumber daya dan pengetahuan desain grafis. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan aplikasi berbasis Augmented Reality (AR) yang dapat membantu UMKM dalam merancang kemasan produk yang lebih menarik dan berkesan. Aplikasi AR ini memungkinkan UMKM untuk memilih jenis kemasan produk mereka dalam bentuk 3D yang interaktif, memungkinkan mereka untuk mengeksplorasi berbagai desain kemasan dan memilih yang paling sesuai dengan jenis produk mereka. Hasil evaluasi awal menunjukkan bahwa aplikasi AR ini dapat mendukung UMKM untuk berkonsultasi dengan para Pendamping Rumah Kemasan Batu Bara sehingga dapat meningkatkan desain kemasan produk mereka, meningkatkan daya tarik produk, dan akhirnya meningkatkan penjualan. Selain itu, aplikasi ini juga memberikan kontribusi positif terhadap pemahaman UMKM tentang teknologi AR dan desain kemasan yang lebih baik. Penelitian ini juga memberikan kontribusi terhadap pemahaman kita tentang bagaimana teknologi AR dapat digunakan dalam mendukung UMKM.Kata kunci: Kemasan; Augmented Reality; UMKM.